PEMBANGKIT ENERGI LISTRIK MEMANFAATKAN PENYERAPAN PANAS JALAN BETON MENGGUNAKAN TEKNOLOGI TERMOELEKTRIK GENERATOR (TEG) DENGAN PELAT PENYERAP TEMBAGA BERBENTUK I - Nurman Saputra; Rahmat Iman Mainil; Azridjal Aziz (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2023)
Heat energy is energy that can be easily found in our daily lives, starting from the heat provided by nature, namely from the sun's heat, heat from chemical reactions, and heat generated by mechanical friction. If this heat energy can be converted into electrical energy, of course it will be able to help meet the increasing energy needs. Thermoelectric generator is a technology that can convert heat energy into electrical energy based on the seebeck effect. This research was carried out by utilizing the absorption of solar radiation heat on a concrete road with class III cast concrete type with K 450 as a thermoelectric generator placed on a medium with dimensions (550 x 300 x 100) mm. The research used 3 modules of thermoelectric generator type SP 1848 arranged in series, a heat sink filled with water and a copper plate in the form of I as an absorbent plate and heat transfer from concrete to TEG. The results of the tests conducted show that the maximum power generated in the concrete produces a power of 14.88 mW with a maximum solar radiation intensity of 1107 W/m2 and the largest temperature difference is 6.7 Â°C. By looking at the power generated continuously, this research allows it to be developed as an alternative energy.